Analisa Sistem Pencatatan Dan Monitoring Piutang Leasing - Tantik Sumarlin; Sukemi Kamto Sudibyo (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2019)
This research was made with the aim to help companies in controlling receivables. The study was conducted on companies engaged in the sale and purchase of motorcycles. These companies act as suppliers of goods and collaborate with credit financing institutions or what is commonly called leasing. Every credit sale will form a lease receivable that must be paid by the related leasing party. In general, many receivables have not been paid from the due date of the agreement. This impedes the company's financial productivity. From these problems, researchers create a system that can be used to meet the needs of the company, in relation to receivables. Researchers create a system that can improve performance to be more effective and dynamic, especially to record the daily control of receivables, namely by using the Leasing Accounts Recording and Monitoring System. The design of recording and monitoring systems for receivables is made using the direct recording method. Systems development methods using the R & D. Method stages in the R & D method include potential problems, information gathering, product design, design validation, design improvement, product testing, product revision, trial use, mass product manufacturing. The design of a monitoring system for leasing receivables billing, can help companies control receivables. Leasing Receivables Recording and Monitoring System can minimize receivables losses.